Complete Submodularity Characterization in the Comparative Independent Cascade Model - Chen, Wei; Zhang, Hanrui (Theoretical Computer Science, 2019)
We study the propagation of comparative ideas or items in social networks. A full characterization for submodularity in the comparative independent cascade (Com-IC) model of two-idea cascade is given, for competing ideas and complementary ideas respectively, with or without reconsideration. We further introduce One-Shot model where agents show less patience toward ideas, and show that in One-Shot model, only the strongest idea spreads with submodularity.